Radial Sizes and Expansion Behavior of ICMEs in Solar Cycles 23 and 24 - Mishra , Wageesh; Doshi , Urmi; Srivastava , Nandita (Frontiers in Astronomy and Space Sciences, 2021)
We attempt to understand the influence of the heliospheric state on the expansion behavior of coronal mass ejections (CMEs) and their interplanetary counterparts (ICMEs) in solar cycles 23 and 24. Our study focuses on the distributions of the radial sizes and duration of ICMEs, their sheaths, and magnetic clouds (MCs). We find that the average radial size of ICMEs (MCs) at 1 AU in cycle 24 is decreased by ∼33% (∼24%) of its value in cycle 23. This is unexpected as the reduced total pressure in cycle 24 should have allowed the ICMEs in cycle 24 to expand considerably to larger sizes at 1 AU. To understand this, we study the evolution of radial expansion speeds of CME-MC pairs between the Sun and Earth based on their remote and in situ observations. We find that radial expansion speeds of MCs at 1 AU in solar cycles 23 and 24 are only 9% and 6%, respectively, of their radial propagation speeds. Also, the fraction of radial propagation speeds as expansion speeds of CMEs close to the Sun are not considerably different for solar cycles 23 and 24. We also find a constant (0.63 ± 0.1) dimensionless expansion parameter of MCs at 1 AU for both solar cycles 23 and 24. We suggest that the reduced heliospheric pressure in cycle 24 is compensated by the reduced magnetic content inside CMEs/MCs, which did not allow the CMEs/MCs to expand enough in the later phase of their propagation. Furthermore, the average radial sizes of sheaths are the same in both cycles, which is also unexpected, given the weaker CMEs/ICMEs in cycle 24. We discuss the possible causes and consequences of our findings relevant for future studies.